Dampak cemaran mikroplastik pada kesehatan masyarakat melalui air minum: Tinjauan literatur - Indana Maya Zulfa; Disny Prajnawita (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Microplastics have increasingly been detected in various drinking water sources, raising concerns about their potential health implications. Variations in concentration, polymer types, and uncertainty in toxicological pathways highlight the need for a comprehensive review. Purpose: To summarize recent scientific evidence on the occurrence of microplastics in drinking water both tap water and bottled water and to assess potential health risks associated with human exposure. Methods: A Systematic Literature Review was conducted following PRISMA 2020 guidelines. Articles were identified through Google Scholar and reputable international journals, limited to the years 2020–2025. Using predefined keywords, 641 studies were screened, and 15 relevant articles met the inclusion criteria. Results: Microplastic levels varied widely across studies and were predominantly composed of PET and PP polymers. Contamination sources included raw water quality, treatment processes, and degradation of plastic packaging. Potential health impacts include gastrointestinal irritation, chemical leaching, and the transport of harmful contaminants. Point-of-Use (POU) technologies demonstrated the highest effectiveness in reducing microplastic before consumption. Conclusion: The presence of microplastics in drinking water is a growing public health concern. Major challenges include inconsistent analytical methods and the absence of standardized exposure limits. Standardized assessment techniques and further toxicological research are needed to support more robust drinking water regulations.   Keywords: Drinking Water; Human Health; Microplastic; Toxicity.